The peculiar mass-loss history of SN 2014C as revealed through AMI radio observations - Anderson, Gemma; Horesh, A.; Mooley, K.; Rushton, A.; Fender, R.; Staley, T.; Argo, M.; Beswick, R.; Hancock, P.; Pérez-Torres, M.; Perrott, Y.; Plotkin, R.; et al. (Oxford University Press, 2017)
We present a radio light curve of supernova (SN) 2014C taken with the Arcminute Microkelvin Imager (AMI) Large Array at 15.7 GHz. Optical observations presented by Milisavljevic et al. demonstrated that SN 2014C metamorphosed from a stripped-envelope Type Ib SN into a strongly interacting Type IIn SN within 1 yr. The AMI light curve clearly shows two distinct radio peaks, the second being a factor of 4 times more luminous than the first peak. This double bump morphology indicates two distinct phases of mass-loss from the progenitor star with the transition between density regimes occurring at 100-200 d. This reinforces the interpretation that SN 2014C exploded in a low-density region before encountering a dense hydrogen-rich shell of circumstellar material that was likely ejected by the progenitor prior to the explosion. The AMI flux measurements of the first light-curve bump are the only reported observations taken within ~50 to ~125 d post-explosion, before the blast-wave encountered the hydrogen shell. Simplistic synchrotron self-absorption and free-free absorption modelling suggest that some physical properties of SN 2014C are consistent with the properties of other Type Ibc and IIn SNe. However, our single frequency data does not allow us to distinguish between these two models, which implies that they are likely too simplistic to describe the complex environment surrounding this event. Lastly, we present the precise radio location of SN 2014C obtained with the electronic Multi-Element Remotely Linked Interferometer Network, which will be useful for future very long baseline interferometry observations of the SN.